Relationship between workers’ return to work, job retention and income in industrial accidents in Korea: a longitudinal study - Jin-Ha Yoon; Tae Hyun Kim; Jong-Uk Won; Suk Won Bae; Inchul Jeong; Seung Wook Lee (BMJ Open)
Objective This study aims to compare workers’ income before and after an occupational injury, with regard to return to work and job retention, over a period of 5 years.Design This study was designed as a longitudinal study.Setting The Panel Study of Workers’ Compensation Insurance (PSWCI) survey targeted workers involved in industrial accidents for which medical care was terminated in the year 2012.Participants The panel study was conducted on a final sample of 2000 workers who were selected proportionally by region (nine regions) after priority assignment by disability rating (six levels). A total of 1458 workers were finally included in this study.Methods This study used data from the first to fifth PSWCI. To identify the effect on income after occupational injury considering return to work and job retention, we used the generalised estimating equation.Results In regard to workers’ return to work, the OR that income after an occupational injury would be higher than that before an occupational injury was 3.17 (2.41–4.17) for those who returned to original work and 2.32 (1.81–2.97) for those re-employed as compared with who did not return to work and 1.27 (1.07–1.15) for those who retained their job as compared with those who did not. The ORs were 2.91 (2.26–3.75) for those who were re-employed and retained jobs and 2.96 (2.15–4.08) for those who returned to original work and did not retain jobs as compared with those who did not return to work and did not retain jobs.Conclusions It is important for accident victims to retain their jobs to maintain their economic status.